PENERAPAN تطبيق الطريقة السقراطية لترقية مهارة الكلام في تعلّم اللغة العربية: Penerapan Metode Sokratik untuk Meningkatkan Keterampilan Berbicara dalam Pembelajaran Bahasa Arab - Rizqi, M. Rizal (Jiluna Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
The learning process in higher education currently still places a lot of emphasis on developing students as individuals who must receive material and rarely develops students as individuals who study material that has been studied or taught by lecturers. Phenomena like this keep students from being enthusiastic about studying the material in more detail based on the problems obtained, and ultimately become the source of the gap in educational outcomes, namely those who learn by understanding the problem will be successful and those who do not understand how to solve the problem will be left behind. With the socratic method in learning Arabic, the main aim is to improve their speaking skills using Arabic by means of continuous communication interaction between lecturers and students. Light communication about daily activities between lecturers and students can ensure that students are always paid attention to and motivated to communicate using Arabic.